Air gap membrane distillation: A detailed study of high saline solution - Nidal Hilal (Desalination, 2017)
An experimental study is used to examine the effect of high concentration of several salts, i.e., NaCl, MgCl2, Na2CO3 and Na2SO4 on permeate flux and rejection factor by air gap membrane distillation (AGMD). A comparative study involving three different membrane pore sizes (0.2, 0.45 and 1.0 μm) were performed to investigate the influence of pore size on energy consumption, permeate flux and rejection factor. The permeate flux decline is higher than that predicted from the vapour pressure reduction. Furthermore, the energy consumption was monitored at different membrane pore size and was found to be increased when the concentration increased.